Perkembangangan peran pecalang sebagai lembaga keamanan adat di masyarakat Bali Indonesia - Kadek Wiwik Indrayanti (Jurnal Cakrawala Hukum, 2021)
The island of Bali is known as one of the world's tourist destinations with all its unique traditions and customary laws. The Balinese have a traditional security institution known as the Pecalang whose role is different from that of the police. The purpose of this article is to identify the position of Pecalang according to Regional Regulation Number 4 of 2019 concerning Traditional Villages and the development of the role of Pecalang. The method used is a mix of methods, namely normative and empirical methods. The results show that the existence of Pecalang is regulated in Law Number 9 of 1979 concerning Village Government and Regional Regulation Number 4 of 2019 concerning Traditional Villages. Pecalang is formed in each of the customary village residents (pekraman) who have the task of maintaining security and order. The role of pecalang is currently experiencing development, which leads to the business, and can even be used as a political tool. What stands out is the case of the closure of the Hare Krsna hostel where the function as a security guard was instead used as a tool by the village to bring order to religious groups or sects that were allegedly not in accordance with community traditions. The police should have been involved because they thought it was a religious matter and their area. The regulation of pecalang duties needs to be re-examined in the Perda so that its function as a guardian of order is clear and not vice versa.How to cite item: Indrayanti, K. (2021). Perkembangangan peran pecalang sebagai lembaga keamanan adat di masyarakat Bali Indonesia. Jurnal Cakrawala Hukum, 12(3), 294-302. doi:https://doi.org/10.26905/idjch.v12i3.7093.